ANALISIS ANTRIAN PADA PT. BNI (PERSERO) TBK. KANTOR LAYANAN UNIVERSITAS MULAWARMAN - Syefira Adina Febri; Anis Rachma Utary; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This research aims to analyze the optimal number of line facilities and service performance at an optimal level. Type of data used is quantitative data and data sources used are primary data that is observation and interview, and secondary data that is library research. Analytical method used was in accordance with the analysis of queuing theory queuing model is applied to the PT. BNI (Persero) Tbk. Service Office Mulawarman University Samarinda Queue Line Regression Models means there is more than one lane facility and there is only one phase of service that must be passed by the customer to complete service.The results showed that the model of the queue used by BNI Service Office Mulawarman University Samarinda is a queue model of Multi Channel - Single Phase by applying queuing discipline namely First Come - First Serve ( FCFS ). The total number of customer arrivals time( λ ) is 33 person/hour and the total value of average number of people served time (μ) is 30 person/hour. Optimal number of tellers in providing customer service is by decreasing 1 teller to the ones originally amounted to 3 tellers. And the result of calculation shows that the queue waiting time at 09.00-10.00 am to be 0,0144 minutes. At 10.00-11.00 am to be 0,0092 minutes. At 11.00-12.00 am to be 0,0071 minutes. At 12.00-13.00 pm to be 0,0077 minutes. The utilization factor at 09.00-10.00 am turns to be 55 %. At 10.00-11.00 am to be 46 %. At 11.00-12.00 am to be 51 %. At 12.00-13.00 pm to be 43 %. and the idle time of teller at 09.00-10.00 am which is previously to be 29 % . at 10.00-11.00 am to be 36 %. At 11.00-12.00 am to be 18 %. At 12.00-13.00 pm 39 %.Key words: Teller, Queuing theory, Multiple channel query system (M/M/S),The optimization of services.